Comparative efficacy and safety of second-line therapies for patients with advanced hepatocellular carcinoma: a systematic review and network meta-analysis of randomized controlled trials - Kang, Fengjiao; Wang, Yin; Cai, Fengqun; Wu, Liuyun; Wang, HuLin; Han, Lizhu; Yin, Qinan; Bai, Lan; Bian, Yuan (Frontiers in Pharmacology, 2025)
BackgroundThe optimal second-line treatment for unresectable hepatocellular carcinoma (HCC) remains uncertain, given variability in efficacy and safety among available therapies. The comparative effectiveness and safety of second-line treatments for advanced HCC were methodically assessed in this network meta-analysis.MethodsA thorough search was conducted up until 20 February 2025, across the PubMed, Medline, Embase, Cochrane Central, and Web of Science databases to find randomized controlled trials (RCTs) evaluating second-line monotherapies (such as Ramucirumab, Regorafenib, Pembrolizumab, Cabozantinib, and Apatinib) in adults with advanced HCC. The main results comprised overall survival and progression-free survival; the supplementary results included objective response rate, disease control rate, and the occurrence of adverse events. A Bayesian random-effects network meta-analysis was employed for data synthesis, with interventions rated according to the SUCRA.ResultsEighteen RCTs involving 6,910 patients were analyzed. Ramucirumab (SUCRA: 69.2%), Regorafenib (67.6%), and Pembrolizumab (66.5%) significantly improved OS compared to control (mean difference [MD]: 2.79 months, 2.80 months, and 2.75 months, respectively). Apatinib (SUCRA: 93.0%; MD: 3.08 months), Cabozantinib (84.8%; MD: 2.65 months), and Regorafenib (48.9%; MD: 1.60 months) provided the most significant PFS benefits. Pembrolizumab (OR: 5.71, 95% CI, 2.71–12.04), Cabozantinib (OR: 5.38, 95% CI, 1.81–16.00), and Apatinib (OR: 5.32, 95% CI, 1.69–16.74) achieved superior ORR, while Apatinib, Cabozantinib, and Regorafenib had the highest DCR (OR: 3.92, 3.67, and 3.31, respectively). Pembrolizumab and Ramucirumab exhibited relatively lower incidences of severe adverse events (grade ≥3 AEs).ConclusionPembrolizumab and Ramucirumab had the most favorable balance of efficacy and tolerability among second-line treatments for advanced HCC and are indicated as optimal therapy alternatives to enhance clinical outcomes.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251010308